(3bUO GdSHjd aj eG aj GddZI GdYQHjI ef GdONjds - (3eMeO Cejf Hf aVd Gddg Hf eMH Gddg Hf eMeO GdeMHj GdMehj, eMH GdOjf , CHh HcQ,J (B1111 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi fYeI GddSGf hHYO , ajbhd deG cGf GdONjd ef GdCdaGX jQfh Yf GdNaGA Qfh GdCdMGX bGd CHh efUhQ (B: (3GYde Cf GdYQH JcdeJ HTF ef GdCYLei s
(3BNQgG (B:s
(3BNQ GdehLhO efgG CKfGA MQa Gdeje , bhdg (B: (3GdeaJdI WYGe eYQha jSei GdBf TYjQjI dchfgG Ydi Tcd GdTYjQ dcfg jMJed GdJChjd hGdMd Ydi GdJaQb s
(3HOGNdgG UaMI (B473 -492 (3HjVGA ai GdCUds
(3HgG fXGe GdJYbjHIs
(3eQJH Ydi QMha GdgLGA hHdZ Hg MQa GdeSes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B41 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B78s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B182 s
Keywords: (3GddZIs